SAT0004 New autoantigen (JKTBP) part of stress granules closes the sensitivity gap in rheumatoid arthritis. (15th June 2017) - Marklein, B; Jenning, M; Muenzer, K; Burmester, G; Skriner, K
Abstract : Background: Rheumatoid arthritis triggers the formation of prion-like stress granules. To investigate which members of the heterogeneous nuclear ribonucleoprotein (hnRNP)-family, components of functionally important subcellular particles are targeted by autoantibodies from RA and other systemic rheumatic diseases. Methods: Using a protein macroarray we identified JKTBP in humans and animal models of inflammatory rheumatic diseases. Bacterially expressed recombinant JKDBP proteins were used to confirm the obtained data. Epitope, TLR7/9 and MyD88 dependency was determined by ELISA. JKTBP expression in cultivated cells and synovial tissue was analysed by indirect immunofluorescence, immunoblot and immunohistochemistry. Results: Anti-JKTBP autoantibodies were detected in 46% of the patients with systemic lupus erythematosus (n=103), in 20–30% of the patients with rheumatoid arthritis (n=286), in 10% of the patients with mixed connective tissue disease (n=20) or spondyloathropathy (n=20), and in <10% of patients with other autoimmune disorders (n=382). Sera positive to JKTBP as well as hnRNP-B1, revealed nearly two thirds of the RF IgM/ CCP2-seronegative patients as early RA patients. Combining sensitivities to all autoantigens tested (JKTBP, AUF1, hnRNP-B1), it was possible to identify 92% of the early RA patients (n=91). In the MRL/lpr mouse model of SLE, mice deficient of MyD88 or TLR7/9 lacked anti-JKTBP autoantibodies, whereas mice deficient of SIGIRR/TIR8 showed enhanced anti-JKTBP autoantibody production. These results show that autoantibody generation against JKTBP, AUF1, hnRNP-B1 is dependent on TLR 7 and TLR9 like rheumatoid factor different to TLR 7 dependent generation of snRNPs. For all tested autoantigens either their titter or generation are dependent on the activation of innate immunity genes MyD88 and SIGIRR/TIR8 gene. In localization, experiments anti-JKTBP autoantibodies specifically stained stress granules (SG) in the cytoplasm. Immunohistochemical studies revealed JKTBP to be highly expressed in SG in the cytoplasm of RA synovial tissue different from OA and normal control tissue Conclusions: These data identify SG as targeted particle in RA and JKTBP as a novel autoantigen in RA, SLE patients and mouse models of inflammatory rheumatic diseases. In combination with the hnRNPs AUF1 and hnRNP-B1, JKTBP autoantibodies close the sensitivity gap in RA left by rheumatoid factor and anti-CCP2 antibodies. Disclosure of Interest: None declared